Case report: Post-traumatic Tourette syndrome resolving with treatment of jugular venous narrowing; reconciling organic brain dysfunction following whiplash trauma with the absence of direct brain injury - Higgins, J. Nicholas P.; Kirker, Stephen (Frontiers in Neurology, 2023)
We describe a man aged 33 years who developed multiple symptoms, personality change, and a severe tic disorder following a road traffic accident, which were undiminished for 3 years until jugular venous narrowing between the styloid process of the skull and the transverse process of the C1 vertebra was treated by surgical decompression. Immediately following surgery, his abnormal movements almost completely resolved, with no regression in 5 years of follow-up. Vigorously debated at the time was whether or not his condition represented a functional disorder. Unrecognized throughout his illness, however, was a complaint of intermittent, profuse discharge of clear fluid from his nose that began on the day of the accident and continued up to the time of surgery, after which it was substantially reduced. This outcome reinforces the idea that jugular venous narrowing can cause or perpetuate a cerebrospinal fluid leak. It suggests that the interaction between these two pathological defects may have a profound effect on brain function in the absence of any demonstrable brain lesion. It invites a reevaluation of normal head and neck venous anatomy. It should strike a cautionary note in the diagnosis of functional illness. It invites exploration of a remediable structural cause for Tourette syndrome.